Is Premarital Guidance Important To Divorce? - Rachmat, Ronald; Setiawan, Tjutjun; Waty, Fries; Lasmaria, Fitry Riny; Hermanto, Yanto Paulus (Budapest International Research and Critics University, 2021)
Divorce in Christian families is seen as a wrong decision and against God's will. Although there are some views from church leaders worldwide regarding divorce, divorce in Christian marriages is not justified. However, based on data from the Indonesian statistical center, divorce cases in Indonesia from 2011 to 2016 have increased significantly. Looking at the facts of divorce cases and the factors that cause divorce, the church has made eftriedrcome or reduced the risk of divorce in Christian marriages. One form of this effort to overcome divorce is to provide premarital guidance for Christian couples who want to deci married. To marrythor will describe the importance of premarital guidance so that from this nation it can help the church to understand the importance of premarital guidance better and carry it out with sincerity and for prospective partners better to understand their respective duties and responsibilities before God so that when conflicts occur in their domestic life, they were able to cope without divorce.